2007
DOI: 10.1111/j.1468-2982.2007.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Symptoms Related to the Percutaneous Closure of An Ostium Secundum Atrial Septal Defect: Report of Four Paediatric Cases and Review of the Literature

Abstract: Several publications have recently suggested that atrial septal defect may be associated with the physiopathology of headache with migraine-type characteristics. We describe four previously asymptomatic paediatric patients with atrial septal defect who underwent percutaneous Amplatzer septal occluder device implantation and who subsequently developed symptoms compatible with migraine headache. The cases had normal echocardiograms after the intervention and a benign course with headache improvement after severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…In four of the case studies (57, 73, 78, 92) antithrombotics ameliorated, reduced, or abolished MA events; in one study, the thienopyridine appeared ineffectual (75). In three studies, MH disappeared at 4 months (92), 6 months (57), and at 9 months (75). However, although MH disappeared in one of the patients, aura without headache persisted at 2-year follow-up (75).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…In four of the case studies (57, 73, 78, 92) antithrombotics ameliorated, reduced, or abolished MA events; in one study, the thienopyridine appeared ineffectual (75). In three studies, MH disappeared at 4 months (92), 6 months (57), and at 9 months (75). However, although MH disappeared in one of the patients, aura without headache persisted at 2-year follow-up (75).…”
Section: Resultsmentioning
confidence: 94%
“…In terms of study type, change in preexisting MH was reported in 3 of 8 case studies (62, 70, 82); 2 of 3 prospective studies (71, 84), and in 9 of 13 retrospective studies (19, 52, 5961, 63, 64, 76, 81). De novo MH was reported in 5 of 8 case studies (57, 73, 75, 78, 92), in 2 of 3 prospective studies (71, 72), and in 11 of 13 retrospective studies (19, 46, 51, 52, 58, 61, 64, 67, 77, 81, 93). Finally, a recent randomized controlled trial reported de novo MH following pASDC (79).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations